(untitled) (Scientific journal of the Fergana State University, 2024)
The article explores how Muriel SPARK used postmodern elements in such works as "The Morning of Miss Jean Brody" and “the Driver’s Seat". Using postmodern elements such as experimental structures, intertextuality and metaphysics, SPARK challenges traditional narrative and perception of reality, thereby making a significant contribution to modern literature.